THE CORRELATION BETWEEN STUDENTS’ LEARNING STYLE AND LEARNING INTEREST ON SCIENCE MATERIAL - Zainal Berlian; Jhon Riswanda; Dian Mutiara; Hendra Pansukna (Al 'Ilmi : Jurnal Pendidikan MIPA, 2016)
The purpose of this research is to know the relation of learning style (visual, auditorial, kinestechtic) with students’ learning interest at VIII class on photosynthesis material in junior high school. Sampling technique in this research used probability proportional to size (PPS). Data collection used questionnaire. The results showed that there is a positive and significant correlation between learning styles with student learning interest in science subjects class VIII with a value of 0.789 are categorized as high correlation and significant value of 10.352. The result of correlation between the dimension of each learning style and the learning interest was obtained by visual learning style - learning interest with correlation value 0.380, auditorial learning style- interest with correlation value 0.673, kinesthetic learning style - interest with correlation value 0.396. This shows the style of auditorial learning has a higher correlation to student learning interest. The results of the calculation of determination coefficient obtained value 59.1% and the remaining 40.9% influenced by other outside factors and research variables. These results also show that learning can affect the level of student interest in learning during the classroom learning process. Therefore, by understanding the learning process in each student , the teacher can make the students' learning interest increase. Keywords: learning style, learning interest, photosynthesis, science